1988
DOI: 10.1103/physrevb.38.3545
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of scanning-tunneling-microscope image profiles and charge-density-wave amplitudes

Abstract: Scanning-tunneling-microscope (STM) studies of 4Hb-TaS& and 4Hb-TaSe2 at 4.2 K show systematic correlation between the charge-density-wave (CDW) amplitude and the STM deflection. The 4Hb phases have both weak and strong CDW's in the trigonal prismatic and octahedral sandwiches, respectively. Scans on opposite faces of the same cleave allow a comparison of the STM response to the two types of CDW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…It also proved to be a new case in which the STM image is sensitive to the electronic states of the sample. Indeed, in a series of works on a variety of CDW materials (for example, 1T -TaS 2 , 1T-TaSe 2 , 2H-NbSe 2 ) the STM was shown to resolve directly both the atomic corrugation and the superimposed CDW modulation, which occurs below a critical temperature [3][4][5][6][7]. The spectroscopic content in STM imaging was not developed there, but rather for the visualisation of different localised electronic states on semiconductor surfaces, for example Si (1, 1, 1), by selecting the bias voltage [8][9][10][11][12][13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It also proved to be a new case in which the STM image is sensitive to the electronic states of the sample. Indeed, in a series of works on a variety of CDW materials (for example, 1T -TaS 2 , 1T-TaSe 2 , 2H-NbSe 2 ) the STM was shown to resolve directly both the atomic corrugation and the superimposed CDW modulation, which occurs below a critical temperature [3][4][5][6][7]. The spectroscopic content in STM imaging was not developed there, but rather for the visualisation of different localised electronic states on semiconductor surfaces, for example Si (1, 1, 1), by selecting the bias voltage [8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…Recently, Whangbo et al have generally reviewed the instabilities of transition metal chalcogenides [15]. In spite of an extensive literature of STM investigations of these materials [2][3][4][5][6][7][15][16][17], a theory of the energy-dependent contrast is conspicuously absent. The specific problem we address is the possible relative change in the phase of the CDW component of the STM image as a function of the bias voltage, in analogy to the case of semiconductors.…”
mentioning
confidence: 99%
“…4,5 STM on 4H b -TaSe 2 was performed with a small negative bias voltage only, and the image of the T layer did show a strong effect due to the (ͱ13aϫͱ13a) superstructure. 15 Again, the pattern of positive and negative z displacements of the tip in STM displays the local density of states of the chalcogen sheet that corresponds to the pattern of positive and negative z displacements of the Se atoms as determined in x-ray diffraction.…”
Section: B Three-dimensional Order Of the Cdwmentioning
confidence: 78%
“…4,6 The possibility of tunneling in the reverse direction was excluded by assuming screening due to the occupied states of the H layers. For STM on the H layers of 4H b -TaSe 2 a weak effect was observed due to the (ͱ13aϫͱ13a) superstructure at a small negative bias and at a low temperature of 4.2 K. 15 Taking into account that thermal broadening of the density of states at the Fermi level is very small at these low temperatures, tunneling obviously cannot explain this image.…”
Section: B Three-dimensional Order Of the Cdwmentioning
confidence: 98%
“…Particularly, the scanning tunneling microscope ͑STM͒ studies by Giambattista et al 5 and Coleman et al 2 showed two completely different kinds of images, one kind with a ͱ13ϫͱ13 charge-density wave ͑CDW͒ and another kind with atomic structures, on the two opposite faces of the same crystal cleave, presumably representing the 1T-type and 1Htype layers. They also showed a mixing of the two images and sometimes a time-dependent change of the image, which might be due to the complex superposition of two images.…”
mentioning
confidence: 99%